Analysis of Causative Factors of Delayed Project Completion (Case Study of Norfa Husada Mother and Child Hospital) - Thoriq, Gerry; Setiawan, Beny; Tanjung, Lailatul Syifa (Journal of Engineering Science and Technology Management, 2026)
Construction project delay is a condition where the execution of work does not proceed according to the agreed schedule. The construction project of Norfa Husada Mother and Child Hospital experienced delays impacting costs and operational time. This study aims to identify the factors causing delays, determine the most dominant factors, and formulate preventive measures. The method used was a questionnaire distribution to 30 respondents directly involved in the project, including contractors, consultants, and project owners. Data were analyzed using descriptive statistics (Mean Rank) with SPSS software. The results show that the Planning Factor is the most dominant cause, specifically due to design changes (redesign) and changes in the scope of work, with a mean value of 1.97. The second dominant factor is the Execution Factor, particularly regarding poor work sequence planning, with a mean value of 1.90. Based on these results, the main strategies to prevent delays include maturing the design planning before construction begins, strengthening coordination between the owner and contractor regarding scope changes, and establishing a more structured method of execution (SOP) in the field.